Behaviour of relative evapotranspiration with agrometeorological stress indices in wheat - BISHNOI, O.P.; SINGH , MOHAN; SINGH, SURINDER (MAUSAM, 1995)
Complex behaviour of stress indices with relative evapotranspiration was observed in early and late sown wheat, however, under normal sown conditions it was linearly decreasing. Predawn leaf water potential and transpiration rate proved to be a stable stress index parameter for characterizing the internal moisture status in the plant as compared to the canopy temperature and stomatal resistance under stress conditions in wheat. Since it is easy to quantify canopy/leaf temperature and within seasonal variations it is widely used for scheduling irrigation and quantigying moisture stress effects on growth and development in wheat.